Perceived consequences of extended social isolation on mental well-being: narratives from Indonesian University Students during the COVID-19 pandemic - Rahiem, Maila Dinia Husni; Abdullah, Steven Eric Krauss @ Abdul Lateef; Ersing, Robin (MDPI AG, 2021)
Despite several recent studies reporting on young people’s well-being during COVID-19, few large-scale qualitative studies have been carried out that capture the experiences of young people from low- and middle-income countries (LMICs) undergoing extended social restrictions. The challenges faced by young people from LMICs during COVID-19 are likely to be amplified by their countries’ large populations, resource constraints, lack of access to health care, living conditions, socio-spatial contexts, and the pandemic’s ramifications for communities. This study explored how youths perceived their well-being after being isolated for one-and-a-half years during the COVID-19 pandemic. Qualitative narrative research was employed as a method of inquiry. One-hundred and sixty-six university students in Jakarta, Indonesia, between the ages of 17 and 22 wrote reflective online essays on the consequences of extended pandemic isolation on their mental health. This data collection strategy offered an in-depth understanding of the phenomenon through the narratives of those who experienced it. Seven themes expressing the youths’ perceived well-being were identified through inductive reflective thematic analysis: (1) the anguish of loneliness and estrangement; (2) a state of “brokenness” resulting from emotional agony and distress; (3) frustration, confusion, and anger; (4) the experience of conflicting emotions; (5) uncertainty about both the present and future; (6) a sense of purpose and fulfillment; and (7) turning to faith. The findings provide important insights into Indonesian youths’ well-being following extended social restrictions following the outbreak. Their collective experiences can be used to inform policy and practice regarding the nature of support mechanisms required both during and following the pandemic, and in the future if such a situation were to occur again.